Resurrection a novel - Steel, Danielle (New York Delacorte Press, 2024)
Darcy Gray's perfect life falls apart when a surprise visit to her husband leads to a horrible shock. She flees to visit her daughter in Paris, where a worldwide health crisis strands her indefinitely. There, she finds refuge with a widowed American engineer and beings to imagine a new life.
114095
Keywords: Married people -- Fiction; Mothers and daughters -- Fiction; Twin sisters -- Fiction; Department stores -- Fiction; Man-woman relationships -- Fiction; Betrayal -- Fiction; Mother-daughter relationship -- Fiction; Paris (France) -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Rome (Italy) -- Fiction; Domestic fiction; Romance fiction; Novels